2014
DOI: 10.3233/bmr-130415
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors associated with low back pain among employees working at a package producing industry

Abstract: Our results identified the risk factors of LBP in a package producing company. The protective approaches aiming to avoid the risk factors could decrease the low back pain prevalence that increases each year passed worked at the company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Forward bending of the trunk is a relatively frequently occurring activity, particularly among blue-collar workers (12). Accordingly, LBP is shown to be more prevalent among blue-than white-collar workers (13). The current ergonomic exposure limits of forward bending are predominantly based on self-reported information, observations of shorter time-periods and ergonomic expert opinions (14).…”
mentioning
confidence: 99%
“…Forward bending of the trunk is a relatively frequently occurring activity, particularly among blue-collar workers (12). Accordingly, LBP is shown to be more prevalent among blue-than white-collar workers (13). The current ergonomic exposure limits of forward bending are predominantly based on self-reported information, observations of shorter time-periods and ergonomic expert opinions (14).…”
mentioning
confidence: 99%
“…The origin of back pain is multifactorial (7), but LBP is a very important estimate of sickness absence (8), indicating that the individual worker's perception of pain is an important element with respect to the consequence for sickness absence, regardless of the underlying pathology. LBP has also been shown to be occupationally related and therefore substantial efforts have been made to identify risk factors for LBP, particularly among blue-collars workers (9,10) where the risk of sickness absence from LBP is higher (8).…”
mentioning
confidence: 99%
“…The prevalence of non specific back pain is consistent with the most previous study 5,6,7 . However, a study has reported a lower incidence rate of back pain among white collar workers 8 . The differences may be due to differences in methodology and term used to define the back pain.…”
Section: Discussionmentioning
confidence: 98%